DEVELOPMENT OF SOLAR ENERGY BASE DEV CHARGING STATION IN COLLEGE CAMPUS - D. Yashwanth Kumar; Rakshita SM; S. Fathima Zohara; Yuvaraj K; Dr. Sharan Reddy; Vijaya Krishna (International Educational Journal of Science and Engineering, 2026)
The rapid adoption of electric vehicles (EVs) demands sustainable charging infrastructure to reduce dependence on fossil fuel-based grid electricity. This project presents the development of a vehicle-mounted solar power generation system for EV charging applications within a university campus environment. The system comprises solar photovoltaic panels mounted on a movable vehicle roof, a Luminous Solar PCU –NXT+ 3.75 KVA inverter with inbuilt Maximum Power Point Tracking (MPPT) charge controller and buck converter, a battery bank of 150 Ah Luminous Solar Tall Tubular batteries, Miniature Circuit Breaker (MCB), and AC switchboard with EV charging outlet. The MPPT controller maximizes solar energy extraction under varying irradiance conditions, while the buck converter regulates voltage for safe battery charging. The inverter converts stored DC power to stable AC power (230V, 50 Hz) suitable for EV charging. Results demonstrate that the system generates sufficient power during peak sunlight hours (11:00 AM – 2:00 PM), with battery storage enabling uninterrupted operation during low sunlight or nighttime. Vehicle mobility allows optimal panel positioning and on-demand power delivery across campus locations. The system reduces grid dependency, lowers carbon emissions, and serves as an effective educational platform for renewable energy technologies. This project validates the feasibility of mobile solar EV charging infrastructure for campus environments, contributing to sustainable transportation and clean energy adoption.